2016
DOI: 10.1021/acs.oprd.6b00180
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Suzuki Reactions in Water with No Added Ligand: Effects of Reaction Scale, Temperature, pH of Aqueous Phase, and Substrate Structure

Abstract: The heterogeneous palladium-catalyzed Suzuki reactions between model aryl bromides (4-bromoanisole, 4-bromoaniline, 4-amino-2-bromopyridine, and 2-bromopyridine) and phenylboronic acid have been successfully conducted in water with no added ligand at the 100-mL scale using 20-40 millimoles of aryl bromide. The product yields associated with these substrates were optimized and key reaction parameters affecting the yields were identified. The results clearly indicate that the reaction parameters necessary to ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 89 publications
(221 reference statements)
2
21
0
Order By: Relevance
“…Previously, it had been reported for SMC reactions that there was a relationship between the change in pH value during the reaction and product yield . The impact of the number of equivalents of K 3 PO 4 base was also studied for this catalytic system (with 500 ppm Pd/ 6 precatalyst solution), and we observed that the rate of the reaction was at least three‐fold faster with 1.2 equivalents of K 3 PO 4 (initial pH value: 10.5, final pH value: 7.5) than with 2 equivalents of K 3 PO 4 (initial pH value: 12, final pH value: 10; Figure , curves a and b).…”
Section: Resultsmentioning
confidence: 57%
“…Previously, it had been reported for SMC reactions that there was a relationship between the change in pH value during the reaction and product yield . The impact of the number of equivalents of K 3 PO 4 base was also studied for this catalytic system (with 500 ppm Pd/ 6 precatalyst solution), and we observed that the rate of the reaction was at least three‐fold faster with 1.2 equivalents of K 3 PO 4 (initial pH value: 10.5, final pH value: 7.5) than with 2 equivalents of K 3 PO 4 (initial pH value: 12, final pH value: 10; Figure , curves a and b).…”
Section: Resultsmentioning
confidence: 57%
“…It was found that the ligand 14b resulted the higher isolated yield and in the absence of any ligands products 16a and 17 were obtained in 68% and 33% isolated yield, respectively (Scheme 4). 15 The ligand 14b was tested in copper-catalyzed homocoupling of 4-methoxyphenylbronic acid (15b) and the desired 4,4′-dimethoxy-1,1′-biphenyl (16b) was obtained in 90% isolated yield. It is notable that in the absence of ligand 14b, the product 16b was obtained in <14% isolated yield (Scheme 4).…”
Section: Paper Syn Thesismentioning
confidence: 99%
“…Even though several hundreds of studies have appeared in the literature, it remains unanswered, even for a simple case, which procedure or catalyst is the best one . On the other hand, several new methodologies have still appeared using several modified conditions including ligands, catalysts, solvent, additives, etc . In this connection and in continuation of our recent research on the development of benign methodologies for C–C coupling, we report here an effective method for SMC using a natural feedstock, water extract of pomegranate ash (WEPA), as a green and sustainable (basic) medium.…”
Section: Introductionmentioning
confidence: 97%
“…Palladium catalysts with appropriate ligands and bases in organic or biphasic media assist as common systems for SMC reactions . The frequently employed ligands for this purpose include phosphines, palladacycles, sterically crowded N ‐heterocyclic carbenes, imines and oximes .…”
Section: Introductionmentioning
confidence: 99%